Governança de bens comuns no Assentamento Estadual Agroextrativista Majari (PA) - BORGES, Marllisson Eriques Araújo (2019)
Using a qualitative approach, this study analyzes the governance of community forest resources in an agroextractive settlement with reference to Elinor Ostrom’s “principles for the collective governance of common goods”. Our study found that the State recognizes the right for community organization, the forms of organization of extractive families, the community’s rules of use, and their monitoring of natural resources. The communities have developed mechanisms to manage resources and protect the territory. However, the absence of state management weakens the sustainability of resources and of a collective agroextractive settlement. We conclude that a multidisciplinary approach is necessary for the construction of these spaces. Otherwise, the future scenario of agroextractive projects may veer towards the overexploitation of forest resources and, in the long term, to their exhaustion due to the action of profiteers who do not participate in the collective action but enjoy the resource.